Manajemen Penyelenggaraan Makanan Berbasis Kepuasan Pasien (Studi Kualitatif di Rumah Sakit Islam Sunan Kudus) - Rahardjo, Franciska; Syaodih, Erliany; Handayani, Nining (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
The provision of meals at RSI Sunan Kudus experienced problems such as staff not understanding the SOP for serving food due to double jobs, patient complaints regarding meals during treatment such as menus and so on. Food management is very important and influences the patient's recovery, so there needs to be an in-depth analysis to find out problems and solutions in managing patient meals. This research is a type of qualitative research with a descriptive observational research design. The research method used is an in-depth interview method with an open research case study type. As a result, it turns out that personnel and infrastructure are important issues in the management of food management at RSI Sunan Kudus. However, the entire process of organizing meals at RSI Sunan Kudus has been carried out well and in accordance with PGRS recommendations. Patient satisfaction in terms of managing patient meals is also said to be sufficient. So, it is necessary to carry out another staff evaluation at RSI Sunan Kudus, especially for the Nutrition Installation so that problems with double-job staff do not become an obstacle in organizing patient meals at RSI Sunan Kudus.